Spent coffee grounds enhanced strength of alkali-hydroxide-free geopolymer concrete: An optimization study - Khong, Sheh Ching; Yee, Jia Jun; Gimbun, Jolius; Tee, Kong Fah; Chin, Siew Choo (Springer, 2025)
This paper presents the development of alkali-hydroxide-free (AHF) geopolymer concrete made of fy ash and spent cofee grounds (SCG) mix. Geopolymers are often formulated with the use of alkali hydroxides, which may have health and safety risks, durability, and workability issues. The addition of acidic materials such as SCG may neutralize the alkali content in geopolymer concrete, hence producing an AHF geopolymer. In this work, the efect of SCG addition ranging from 0 to 10% on the geopolymer strength cured from 7 to 90 days was studied. The optimum curing period and SCG addition that can yield the highest strength were optimized using response surface methodology (RSM). It was found that the geopolymer concrete containing 1.85% SCG cured for 75 days has the highest compressive strength of 12.78 MPa. The AHF geopolymer demonstrated 6.8% higher acid resistance than the control mix. This work demonstrated the contribution of SCG in the formation of an AHF geopolymer with enhanced strength.